2011
DOI: 10.12693/aphyspola.119.52
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Interactions and Some Magnetic Properties of Nanocrystalline Co40Fe50Ni10and Co50Fe45Ni5Alloys Prepared by Mechanical Synthesis and Subsequently Heat Treated

Abstract: Co40Fe50Ni10 and Co50Fe45Ni5 ternary alloys were prepared by mechanical alloying method. To check the stability of their structure thermal treatment was applied subsequently. As X-ray diffraction studies proved the final products of milling were the solid solutions with bcc lattice and the average grain sizes ranged of tens of nanometers. After heating of the Co50Fe45Ni5 alloy up to 993 K the mixture of two solid solutions with bcc and fcc lattices was formed. In other cases thermal treatment did not change th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Due to the heterogeneous nature, a range of lattice spacing measurements were recorded mostly falling within the 0.20–0.25 nm range. The 0.25 nm lattice measurement shown within the HRTEM inset in Figure falls within normal lattice spacing range for FCC FeCoNi alloys and FCC CrFeCoNi alloys for the (111) plane both before and after HER–OER catalytic testing. As observed in the XRD pattern, the 2θ shifts resemble the FCC CrFeCoNi alloy more closely (Figure S8c).…”
Section: Resultssupporting
confidence: 55%
“…Due to the heterogeneous nature, a range of lattice spacing measurements were recorded mostly falling within the 0.20–0.25 nm range. The 0.25 nm lattice measurement shown within the HRTEM inset in Figure falls within normal lattice spacing range for FCC FeCoNi alloys and FCC CrFeCoNi alloys for the (111) plane both before and after HER–OER catalytic testing. As observed in the XRD pattern, the 2θ shifts resemble the FCC CrFeCoNi alloy more closely (Figure S8c).…”
Section: Resultssupporting
confidence: 55%
“…7,8,15 We found in XRD spectra that catalyst 2 shows higher intensity peaks overall than the peaks in catalyst 1's XRD spectra (Figure S9a and S10a), and therefore suggests a more overall crystalline structure in catalyst 2. We also found that the XRD diffraction peaks for catalyst 1 indicate a similar match to a ternary metal alloy reference of Fe0.5Co0.4Ni0.1, 34 while catalyst 2 indicates a similar match to a ternary metal alloy reference of Fe0.33Co0.48Ni0.19. 35 While neither catalyst showed metal oxide peaks before electrochemical testing, catalyst 1 exhibited low intensity NiO peaks 36 after electrochemical testing.…”
Section: Resultsmentioning
confidence: 53%
“…17,37 HRTEM measurements of the lattice spacing of the nanocrystalline particles (Figure S9b, S10b) yielded spacings of 0.20 nm for catalyst 1 and 0.18 nm for catalyst 2, which match well to their XRD (111) and ( 200) plane reference values respectively. 34,35 We analyzed both catalysts with STEM and EDS mapping after LSV and observed the presence of particles containing Fe, Ni, and Co (with higher amounts of Ni and Co compared to Fe), dispersed within a primarily iron oxide matrix (Figure 3a and Figure S9b, S10b). Catalyst 1 had particle sizes averaging ~10 nm in diameter (Figure 3a and Figure S11), while catalyst 2 had a more polydisperse particle size range of ~2-11 nm (Figure S9b and Figure S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alloys were disordered solid solutions, characterized by the bcc, or fcc crystalline lattice of the regular system. Detailed structural investigations were presented earlier in works [23][24][25][26]. Figure 1a presents, as an example, room-temperature Mössbauer spectra for mechanosynthesized Co 40 Fe 40 Ni 20 system, recorded at various stages of milling process.…”
Section: Resultsmentioning
confidence: 99%